Comparison of oncogenic HPV type‐specific viral DNA load and E6/E7 mRNA detection in cervical samples: Results from a multicenter study. Issue 3 (26th December 2012) - Broccolo, Francesco; Fusetti, Lisa; Rosini, Sandra; Caraceni, Donatella; Zappacosta, Roberta; Ciccocioppo, Lucia; Matteoli, Barbara; Halfon, Philippe; Malnati, Mauro S.; Ceccherini‐Nelli, Luca
Abstract High‐risk human papillomavirus (HR‐HPV) genotype viral load and E6/E7 mRNA detection are proposed as surrogate markers of malignant cervical lesion progression. Currently, the use of commercially available DNA‐based or mRNA‐based tests is under investigation. In this study, the viral DNA load and E6/E7 mRNA detection of the five most common HR‐HPV types detected in cervical cancer worldwide were compared in 308 cervical samples by using in‐house type‐specific quantitative real‐time PCR assays and PreTect HPV‐Proofer test, respectively. Sensitivity and negative predictive values were higher for the HPV‐DNA assays combined (95.0% and 96.0%, respectively) than the RNA assays (77.0% and 88.0%, respectively); conversely, the mRNA test showed a higher specificity and higher positive predictive value (81.7% and 66.9%, respectively) than the DNA test (58.6% and 52.5%, respectively) for detecting histology‐confirmed high‐grade cervical intraepithelial neoplasia. A significantly higher association between viral DNA load and severity of disease was observed for HPV 16 and 31 (γ = 0.62 and γ = 0.40, respectively) than for the other HPV types screened. A good degree of association between the two assays was found for detection of HPV 16 (k = 0.83), HPV 18 (k = 0.72), HPV 33 (k = 0.66), and HPV 45 (k = 0.60) but not for HPV 31 (k = 0.24). Sequence analysis in L1 and E6‐LCR regions of HPV 31 genotypes showed a high level of intra‐type variation. HR‐HPV viral DNA load was significantly higher in E6/E7 mRNA positive than negative samples (P < 0.001), except for HPV 31. These findings suggest that transcriptional and replicative activities can coexist within the same sample. J. Med. Virol. 85:472–482, 2013. © 2012 Wiley Periodicals, Inc.